For the following system, use the second equation to make a substitution for y in the first equation.

3x + y = 1
y + 4 = 5x

What is the resulting equation?

3x + 5x - 4 = 1
3x + 4 - 5x = 1
3x + 5x + 4 = 1

Respuesta :

CPED

Answer:

Option A:  3x + 5x - 4 = 1

Step-by-step explanation:

Given equations:

3x + y = 1  ------------ eq1

y + 4 = 5x ---------- eq2

eq2 can also be written as:

y = 5x - 4 ----------- eq3

By substituting value of y from eq 3 into eq1, the resulting equation will be:

3x + 5x - 4 = 1

i hope it will help you!

Answer:

Option A:  3x + 5x - 4 = 1

Step-by-step explanation:

Given equations:

3x + y = 1  ------------ eq1

y + 4 = 5x ---------- eq2

eq2 can also be written as:

y = 5x - 4 ----------- eq3

By substituting value of y from eq 3 into eq1, the resulting equation will be:

3x + 5x - 4 = 1

i hope it will help you!